Effects of consolidation processing parameters on the surface morphology and void content of braided thermoplastic composite tubes. (20th August 2021) - Kwon, Boseong; Choi, Wonwoo; Ju, Hyunwoo; Kweon, Jin-Hwe; Nam, Young-Woo
Abstract: In this study, the consolidation process of radial-type braided carbon fiber reinforced polyetherketoneketone (CF/PEKK) thermoplastic composite tubes was investigated. Braided tube preforms were fabricated by braiding at the lamination angles of [±70/±204 /±70/±204 /±70] on 75 mm mandrels using 6.35 mm tapes and 48 or 72 bobbins. The CF/PEKK tubes were fabricated through the vacuum consolidation process inner mold line (IML) using a mandrel, the vacuum consolidation process outer mold line (OML) using an outer mold, and the OML-polytetrafluoroethylene (PTFE) consolidation process using an external mold and a PTFE bladder. The effects of vacuum pressure, caul plate or PTFE bladder on the consolidation were analyzed. The consolidation processes were evaluated by the surface morphology, void content, and crystallinity of the consolidated tubes. When the vacuum pressure increased from 10 to 30 inch Hg in the IML process, the void content of the thermoplastic tube increased, but there was no change in the surface wrinkle pattern. Furthermore, the use of a caul plate increased the void content of the tube. The OML process resulted in a high void content above 20% regardless of caul plate use; thus, it was considered inappropriate as a tube consolidation process. Although the OML-PTFE tube showed an uneven surface defect, a flat surface without wrinkles and a low void content of 0.5% were observed. The results of this study confirmed that the proposed OML-PTFE consolidation process of CF/PEKK is applicable to the manufacture of thermoplastic composite tubes used in actual aircrafts.